Determinants of husbands’ readiness to provide birth support during childbirth in maternal care settings - Lia Aprilianti; Triana Indrayani; Andi Julia Rifiana; Vivi Silawati (KHD-Production, 2026)
Maternal mortality serves as a critical barometer of global health equity, exposing profound disparities in access to quality services across socioeconomic strata. Elevated maternal mortality rates (MMR) are driven by multifactorial challenges, including compromised maternal health status, inadequate pregnancy readiness, insufficient antenatal care, and limited access to skilled birth attendance. This study aimed to analyze childbirth companion readiness at the maternity clinic. This study used a quantitative, cross-sectional design. The sample comprised 65 prospective birth companions. The data were analyzed using univariate, bivariate, and multivariate logistic regression tests. The study showed that most respondents had a low level of readiness (53.8%). Statistically significant relationships were observed between knowledge, compliance, attitude, perception, economic status, religiosity, leadership style, and physical readiness and readiness to assist childbirth (p < 0.05). However, no significant relationship was found between occupation and cultural factors with readiness. Multivariate analysis indicated that knowledge was the most dominant variable influencing readiness, with a beta coefficient of 9.914 and a p-value of 0.002 (< 0.05). Knowledge is the most dominant factor influencing the readiness of birth companions. Midwives provide education and communication to prospective birth companions (husbands) to improve childbirth readiness.